2017
DOI: 10.1186/s40893-017-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between urinary symptoms assessment and objective bladder dysfunctions in multiple sclerosis

Abstract: Objective: To assess the association between objective bladder function parameters in relation to urinary symptoms, and to analyze the sensitivity and specificity of subjective urinary symptom-assessment in predicting objective bladder dysfunction in a multiple sclerosis (MS) population. Methods: Consecutive MS patients with Expanded Disability Status Score (EDSS) ≤7.0 were included in this prospective study. In a single visit, patients were evaluated for the presence of urinary symptoms, then assessed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
4
0
3
Order By: Relevance
“…There was no statistically significant correlation between the complaints of NLUTD reported by patients with MS and the results of urodynamic examinations. This conclusion is confirmed by some other authors (Amundsen et al, 1999;Wiedemann et al, 2013;Haggiag et al, 2017;Fragalà et al, 2015). Blaivas found that a treatment based exclusively on reported symptoms was ineffective for at least 50% of patients with MS (Blaivas, 1980).…”
Section: Discussionsupporting
confidence: 70%
“…There was no statistically significant correlation between the complaints of NLUTD reported by patients with MS and the results of urodynamic examinations. This conclusion is confirmed by some other authors (Amundsen et al, 1999;Wiedemann et al, 2013;Haggiag et al, 2017;Fragalà et al, 2015). Blaivas found that a treatment based exclusively on reported symptoms was ineffective for at least 50% of patients with MS (Blaivas, 1980).…”
Section: Discussionsupporting
confidence: 70%
“…The limitations of our study are the relatively small number of individuals who underwent assessment, but the demographic characteristics of our patient population was within the range of the previously reported studies [8][9][10]12]. Patients were also taken from those referred to a tertiary uroneurology service, so may have more severe LUT symptoms than the overall population of patients with MS.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, as the bladder/bowel FSS only ranges from 0–3, it does not sufficiently delineate the severity nor fully encapsulate the nature of symptoms. Severity of LUT symptoms as assessed by unstructured interview also did not predict objective measures of LUT dysfunction including PVR, Qmax and the presence of detrusor-sphincter dyssynergia [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nach Haggiag et al. taugt die nichtstandardisierte Miktionsfrequenz mit einer Sensitivität von nur 26,3 % nicht als Prädiktor einer gestörten Harnblasenfunktion [ 14 ]. Die standardisierte Miktionsfrequenz korrelierte in unserer Studie gut mit einer Detrusorüberaktivität (OR = 1,16; KI:[1,07–2,06]), sodass „first-line“ eine orale oder transdermale detrusordämpfende Therapie mit Antimuskarinika gerechtfertigt ist (Tab.…”
Section: Diskussionunclassified